Computer-based instrumentation system for temperature measurement using thermocouple in visual basic application (C.I.S.T.V.A.) - Muhamad Akmal, Ishak (2008)
In this project, Visual Basic is used as a main programming language to develop a GUI (Graphical User Interface) application. This application is developed to help student in studying the industrial instrumentation subject. For this project, thermocouple sensor type K will be used as an input device to detect temperature changes. The input will be converted into current signal between 4 - 20mA. Then, a DAQ card will be used to interface between the instrument and computer. The software is divided into 4 sections, data preview, data control, application and setting. Data preview section is used to preview live data from DAQ card. When the data is completely recorded, the data is manipulated to get appropriate result and graph, using data control section. In application section, some useful applications have been added for student such as converter, uncertainty calculation, graph generator, live graph, export data, data recorder and data plotter. And the setting section has function for software’s setting.